Angiogenic cytokines and their influence on circulating tumour cells in sera of patients with the primary diagnosis of breast cancer before treatment. Issue 1 (December 2016) - Vilsmaier, Theresa; Rack, Brigitte; Janni, Wolfgang; Jeschke, Udo; Weissenbacher, Tobias
Abstract Background Circulating tumour cells (CTCs) have been found to be a prognostic marker for reduced disease free survival, breast cancer–specific survival, and overall survival before the start of systemic treatment. Methods A total of 200 patients' sera were included in this study, 100 patients being CTC positive and 100 patients being CTC negative. Matching criteria were histo-pathological grading, lymph node metastasis, hormone receptor status, TNM classification and survived breast cancer patients vs. deceased tumor associated patients. A multi cytokine/chemokine array was used to screen the sera for the angiogenic markers. Results Statistical significant correlation was exposed for sFlt1 values in regard to the CTC-Status. CTC negative patients displayed increased sFlt1 expression opposed to CTC positive breast cancer patients. Furthermore, significant enhanced PIGF values were also disclosed in CTC negative patients compared to patients being CTC positive. Analyzing the living patient collective we found significant differences in sFlt1 and PlGF values in regard to CTC negative and CTC positive patients. Conclusion Both vascular markers showed enhanced expression in the CTC negative patient collective. To continue, the collective graded G2 showed significantly enhanced sFlt1 expressions amongst patients with no CTCs. Moreover, the patient collective with no lymph node metastasis and CTC negativity indicated statistically significant increased sFlt1 values. A functional interaction of sFlt1 and PlGF was found, suggesting that their overexpression in tumour cells inhibits CTCs entering the peripheral blood. Furthermore, in regard to CTC negativity, sFlt1 and PlGF values may potentially serve as predictive markers. Trial registration The TRN of this study isNCT02181101 and the date of registration was the 4th of June 2014. The study was retrospectively registered.